Study of Spot Welding of Austenitic Stainless Steel Type 304 - Shamsul Baharin Jamaludin, Assoc. Prof. Dr.; M.M. Hisyam; Shaiful Rizam Shamsudin; Murizam Darus; Mohd Fitri Mohamad Wahid (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.